Optimisation of Growth Yield and Quality of Strawberry Cultivars through Organic Farming (Journal of Environmental Science and Natural Resources, 2019)
Adoption of organic farming has been increased which have a reduced impact on environment. An experiment was conducted at the Landscaping section and Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh for optimisation of growth, yield and quality of strawberry cultivars through organic farming during the period from October 2017 to March 2018. The experiment comprised two cultivars viz., RU-1 (Festival) and RU-2 (AOG), and eight organic manures viz., control, cowdung, mustard oilcake (MOC), poultry manure, cowdung+MOC, cowdung+poultry manure, MOC+poultry manure, cowdung+MOC+poultry manure. The two-factor experiment was laid out in randomised complete block design with three replications. Significant variation was observed between strawberry cultivars and organic manures in all the parameters studied. Highest growth, yield and quality characters were obtained from Festival except number of runner per plant and TSS content with AOG. Combined application of cowdung+MOC+poultry manure gave the maximum yield (19.14 t/ha) than the other treatments.J. Environ. Sci. & Natural Resources, 11(1-2): 121-129 2018